The Diplomatic Activity of the Plenipotentiary Representative of the Republic of Armenia G. Pasdermadjian (Armen Garo) in the USA at the End of 1919 - Ghambaryan, Armenuhi (ՀՀ ԳԱԱ)
In early October 1919, a special delegation led by the former Prime Minister of the First Republic of Armenia, H. Kajaznuni, traveled to the United States. The delegation’s purpose was not only to appeal to the American government for humanitarian assistance on behalf of the Council of Armenia but also to ensure the resolution of political issues. Among these, recognition of Armenia as an Independent Republic was a top priority among them. 1919 թ. հոկտեմբերի սկզբին Հայաստանի Առաջին հանրապետության անդրանիկ վարչապետ Հ. Քաջազնունու գլխավորությամբ հատուկ պատվիրակություն է մեկնում ԱՄՆ։ Պատվիրակությունը լիազորված էր ոչ միայն Հայաստանի Խորհրդի անունից դիմելու Ամերիկայի Միացյալ Նահանգների կառավարությանը՝ հումանիտար օգնություն հատկացնելու խնդրանքով, այլև քաղաքական խնդիրների լուծումներն ապահովելու իրավունքով: Դրանց մեջ առաջնայինը Հայաստանի Հանրապետության ճանաչման հարցն էր։ В начале октября 1919 г в США отбыла специальная делегация во главе с первым премьер-министром Первой Республики Армения О. Качазнуни. Делегация была уполномочена не только обращаться от имени Совета Армении к правительству США за гуманитарной помощью, но и правом обеспечения решения политических проблем. Среди последних приоритетным было признание Республики Армения.
Keywords: History